Health Informatics: Three key themes and the academic-professional context - Cobarsí-Morales, Josep (Anuario ThinkEPI, 2018)
In this article we discuss a conceptual approach to Health Informatics. We then review the status, trends, and main challenges in relation to three themes in the development of this field: patient empowerment, equity in health, and data science application to health. We conclude with a brief review of the academic context and professional associations, both in Spain and at the international level.